Asymmetric Information and Imperfect Competition in Lending Markets - Crawford, Gregory S.; Pavanini, Nicola; Schivardi, Fabiano (American Economic Review, 2018)
We study the effects of asymmetric information and imperfect competition in the market for small business lines of credit. We estimate a structural model of credit demand, loan use, pricing, and firm default using matched firm-bank data from Italy. We find evidence of adverse selection in the form of a positive correlation between the unobserved determinants of demand for credit and default. Our counterfactual experiments show that while increases in adverse selection increase prices and defaults on average, reducing credit supply, banks’ market power can mitigate these negative effects. (JEL D22, D82, G21, G32, L13, L25)